2001
DOI: 10.1093/carcin/22.6.891
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitory effects of diallyl disulfide on human breast cancer cell lines

Abstract: Diallyl disulfide (DADS) is an oil-soluble organosulfur compound found in garlic. The effect of synthetic DADS on the growth of estrogen receptor (ER)-positive (KPL-1 and MCF-7) and -negative (MDA-MB-231 and MKL-F) human breast cancer cell lines was examined. In an in vitro MTT assay, regardless of ER status, DADS at an IC(50) of 1.8-18.1 microM after 72 h incubation caused inhibition of growth in all four cell lines examined. Growth inhibition was due to apoptosis as seen by the appearance of a sub G1 fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(128 citation statements)
references
References 40 publications
6
115
1
6
Order By: Relevance
“…The DADS-induced apoptosis in colon cancer cells correlated positively with an increase in the level of intracellular free calcium (Sundaram and Milner, 1996). In MDA-MB-231 human breast cancer cell line, the DADS-induced apoptosis was associated with upregulation of Bax, downregulation of Bcl-X L and activation of caspase-3 (Nakagawa et al, 2001). The DATS-induced apoptosis in BGC823 human gastric cancer cell line was associated with downregulation of Bcl-2 and activation of caspase-3 (Lan and Lu, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The DADS-induced apoptosis in colon cancer cells correlated positively with an increase in the level of intracellular free calcium (Sundaram and Milner, 1996). In MDA-MB-231 human breast cancer cell line, the DADS-induced apoptosis was associated with upregulation of Bax, downregulation of Bcl-X L and activation of caspase-3 (Nakagawa et al, 2001). The DATS-induced apoptosis in BGC823 human gastric cancer cell line was associated with downregulation of Bcl-2 and activation of caspase-3 (Lan and Lu, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…More recent studies including those from our laboratory have revealed that some naturally occurring OSC analogues can inhibit proliferation of cultured cancer cells by causing apoptosis and/or cell cycle arrest (Sundaram and Milner, 1996;Milner, 1998, 2000;Nakagawa et al, 2001;Robert et al, 2001;Shirin et al, 2001;Kwon et al, 2002;Li and Lu, 2002;Filomeni et al, 2003;Xiao et al, 2003;Lan and Lu, 2004;Xiao et al, 2004). Milner and co-workers were the first to report apoptosis induction and cell cycle arrest by DADS in human colon cancer cells (Sundaram and Milner, 1996;Milner, 1998, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…This is supported by the very low percentage of viable cells seen after only 24 h. The compounds 2-5 and 19 significantly inhibited the growth of HeLa and DU-145 cells in vitro, possibly by either down-regulation of antiapoptotic Bcl-X L and up-regulation of proapoptotic Bax or by increasing the p21 waf1/cip1 protein, which is involved in cell cycle arrest in G 1 or G 2 phase. 36 Copeland et al has reported that 2,3-dichloro-5,8-dimethoxy-1,4-naphthoquinone exhibits cytoxicity on androgen-dependent and -independent prostate cancer cell lines inducing apoptosis by arresting cell cycle at G 1 phase. 37 The cell cycle alterations indicate that cell cycle arrest is one of the primary mechanisms responsible for the anticancer activity of synthesized 7-MJ derivatives in HeLa and DU-145 cells.…”
Section: Analysis Of Apoptosismentioning
confidence: 99%
“…Garlic oil, or more specifically its diallyl disulfide (DADS) content, has become a quite appealing anti-carcinogenic agent. This is due, in part, to its ability to induce apoptosis in vitro (4) and to inhibit the formation and growth of tumors in vivo (5,6). DADS has been shown to inhibit the in vitro and in vivo growth of breast, liver, lung, gastric, colon, and prostate cancers, as well as neuroblastoma and leukemia cell lines (5,(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%